HIF-1α Alleviates High-Glucose-Induced Renal Tubular Cell Injury by Promoting Parkin/PINK1-Mediated Mitophagy - Yu, Lu; Wang, Yulin; Guo, Yan Hong; Wang, Liuwei; Yang, Zijun; Zhai, Zi Han; Tang, Lin (Frontiers in Medicine, 2022)
It is well-established that mitophagy leads to Diabetic Nephropathy (DN) and renal failure. Mitophagy mediated by a Hypoxia-inducible factor-1α (HIF-1α) plays a beneficial role in many diseases. Nevertheless, the mechanisms underlying HIF-1α-mediated mitophagy in DN remain unclear. This study defines the role of HIF-1α mediated mitophagy in DN. The expression of HIF-1α was upregulated in HK-2 cells in an High-Glucose (HG) environment, and the YC-1 (a specific inhibitor of HIF-1α) further exacerbated the hypoxia-induced mitochondrial dysfunction. Conversely, the HIF-1α-mediated protective effect was strengthened by scavenger N-acetylcysteine (NAC), a type of reactive oxygen species. Moreover, HIF-1α-Parkin/PINK1-mediated mitophagy prevented apoptosis and ROS production in HK-2 cells subjected to HG exposure. In summary, HIF-1α mediated mitophagy on HK-2 cells under HG conditions could alleviate DN, suggesting that it has huge prospects for DN treatment.